Família e escola: como promover essa interação? - SOUZA, Rosângela dos Santos (2022)
This study comes from a research that is subject to the subject: School and family: how to promote this interaction, where its main focus is to know what the elementary School of Education CASTRO ALVES has done to promote their interaction with the families of their Students, whereby both can establish a solid and effective partnership, aiming to promote a constructive, fair and quality education through collective work. For this, it was held at first, a theoretical basis, based mainly on the works of Castro and Regattieri (2009), Chaves (1994), Gimeno (2001), Paro (2007), Prado (1985) and Valle (2011). Then a field survey was carried out, whereby it was possible to make a survey on the relationship between the school EMEF CASTRO ALVES and the parents and/or responsible for the students who attend it. For the collection of the data, a questionnaire consisted of 11 (eleven) questions to the parents of students attending the school, field of research, was applied. The results revealed that the interaction between the school researched with the families of their students has been unsatisfactory, since, parents have not followed closely the school performance of their children, claiming the lack of time, the lack of openness and incentive for Part of the direction of the school and of the teachers and lack of interest in wanting to participate in the events of the school. The school, in turn, has accepted this reality in a manner, since nothing has been done to change that situation. In this way, it was sought at the end of this work, to suggest that the information acquired through this, be applied in the daily life of the school-field, with the purpose of promoting, day after day, the partnership and the interaction between family and school, aiming at the solution of the problems related to the process teaching learning, as well as, contributing to the construction of a Democratic school and a really transforming education.